Nonlinear Dynamic Analysis of Multi-component Mooring Lines Incorporating Line-seabed Interaction - Kurian, V.J. (2013)
Abstract: In this study, a deterministic approach for the dynamic analysis of a multi-component mooring line was formulated. The floater motion responses were considered as the mooring line upper boundary conditions while the anchored point was considered as pinned. Lumped parameter approach was adopted for the mooring line modelling. The forces considered were the submerged weights of mooring/attachment, physical/added inertia, line tension, fluid/line relative drag forces and line/seabed reactive forces. The latter interactions were modelled assuming that the mooring line rested on an elastic dissipative foundation. An iterative procedure for the dynamic analysis was developed and results for various mooring lines partially lying on different soils were obtained and validated by conducting a comparative study against published results. Good agreement between numerical and published experimental results was achieved. The contribution of the soil characteristics of the seabed to the dynamic behaviour of mooring line was investigated for different types of soil and reported. Keywords: Fluid drag force, lumped mass method, multi-component mooring line, moored floating structure, semisubmersible platform